Gastrointestinal Bleeding in COVID-19 Patients: A Rapid Review. (13th July 2022) - Negro, Alessandra; Villa, Giulia; Rolandi, Stefano; Lucchini, Alberto; Bambi, Stefano
Abstract : The incidence of COVID-19 gastrointestinal manifestations has been reported to range from 3% to 61%. There are limited data on the incidence rates and risk factors associated with gastrointestinal bleeding (GIB) in patients with COVID-19. A rapid review has been designed to investigate whether there is a relationship between COVID-19 and GIB in adult patients. PubMed, CINAHL, EMBASE, Cochrane Library, and Scopus databases have been analyzed. A total of 129 studies were found; 29 full texts were analyzed, and of these, 20 were found to be relevant to the topic. The key findings of the included studies present an overall GIB rate in COVID-19 patients ranging from 1.1% to 13%. The bleeding involves mucosal damage of the duodenum, stomach, colon, and rectum. The management of gastrointestinal bleeding could be conservative. The use of fecal diversion systems for the management of diarrhea in COVID-19 patients should be minimized and closely evaluated for the risk of rectal mucosal damages and erosions. It is recommended to provide an accurate nutritional assessment; an early setting up of enteral nutrition, if not contraindicated, can help protect the gut mucosa of patients and restore normal intestinal flora. Larger cohort studies are needed to increase the information about this topic.